Study protocol of a pilot randomised controlled trial assessing the feasibility and acceptability of RecoverEsupport: a digital health intervention to enhance recovery in women undergoing surgery for breast cancer - Christopher Oldmeadow; Mitch J Duncan; Penny Reeves; Priscilla Viana da Silva; Rebecca Wyse; Helen Moore; Alison Zucca; Sancha Robinson; Stephen Ridley Smith; Emma Sansalone; Owen Morris; Rebecca Chenery; et al. (BMJ Open)
Introduction Internationally, breast cancer is the second most diagnosed cancer with approximately 2.3 million people diagnosed each year. 40% will require a mastectomy which has an average length of hospital stay of 1–2 days. Enhanced Recovery After Surgery (ERAS) guidelines include the following patient-managed recommendations: early mobilisation, early eating and drinking, opioid minimisation and physiotherapy exercises. Low adherence rates to these recommendations suggest that patients need support to do these things. A digital health intervention (DHI) may provide an effective, cost-effective and scalable solution. This pilot trial aims to assess the feasibility of conducting a trial of RecoverEsupport and the acceptability of the RecoverEsupport intervention to support patients to recover from breast cancer surgery.Methods and analysis Participants will be recruited from the perioperative clinic and breast surgery units at a major cancer hospital in New South Wales, Australia and randomised (1:1) to receive (1) control: usual care or (2) intervention: usual care plus RecoverEsupport. The DHI incorporates the following evidence-based behaviour change strategies: education, self-monitoring and feedback and prompts and cues. The primary trial aims are to assess the feasibility of the trial and the acceptability of the RecoverEsupport intervention. The secondary aims are to assess preliminary efficacy and cost-effectiveness regarding the length of hospital stay. Data regarding patient behaviours related to patient-managed ERAS recommendations, Quality of Life, European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30), Quality of Recovery (QOR-15), Anxiety (Hospital Anxiety and Depression Scale), hospital readmissions, emergency department presentations and health service utilisation postdischarge will also be collected.Ethics and dissemination This study has been approved by the Human Research Ethics Committees of the Hunter New England Local Health District (2022/ETH02010), the University of Newcastle (H-2023–0298) and the Calvary Mater Newcastle (2022/STE03757). Trial outcomes will be disseminated via peer-reviewed publications and conference presentations.Trial registration number Australian New Zealand Clinical Trials Registry (ANZCTR) ACTRN12624000417583.